2015
DOI: 10.1186/s40555-014-0097-0
|View full text |Cite
|
Sign up to set email alerts
|

Guanaco abundance and monitoring in Southern Patagonia: distance sampling reveals substantially greater numbers than previously reported

Abstract: Background: Guanacos (Lama guanicoe) are thought to have declined in Patagonia mainly as a result of hunting and sheep ranching. Currently accepted estimates of total population size are extrapolated from densities obtained through strip transects in local studies. We used road surveys (8,141 km) and distance sampling to estimate guanaco density and population size over major environmental gradients of Santa Cruz, a large region in southern Patagonia. We also calculated the survey effort required to detect pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 31 publications
1
21
0
2
Order By: Relevance
“…To compare our results with those reported for other areas of the guanaco distribution range, we considered studies with reported measures of error of up to 30%. Our densities are in accordance with reports for Argentinian Patagonia (ranging between 0.95–7.56 ind/km 2 ) [ 54 – 56 ] and for the Provincial Park Ischigualasto (0.12 ind/km 2 ) [ 57 ], although other studies reported larger figures (ranging 3.25–26 ind/km 2 ) respectively, for other protected areas [ 37 , 58 , 59 ]. Of special interest is the study on the Chilean sector of Tierra del Fuego that reports 30.5 ind/km 2 [ 60 ], a value one order of magnitude larger than ours.…”
Section: Discussionsupporting
confidence: 92%
“…To compare our results with those reported for other areas of the guanaco distribution range, we considered studies with reported measures of error of up to 30%. Our densities are in accordance with reports for Argentinian Patagonia (ranging between 0.95–7.56 ind/km 2 ) [ 54 – 56 ] and for the Provincial Park Ischigualasto (0.12 ind/km 2 ) [ 57 ], although other studies reported larger figures (ranging 3.25–26 ind/km 2 ) respectively, for other protected areas [ 37 , 58 , 59 ]. Of special interest is the study on the Chilean sector of Tierra del Fuego that reports 30.5 ind/km 2 [ 60 ], a value one order of magnitude larger than ours.…”
Section: Discussionsupporting
confidence: 92%
“…Departments were obtained from (SENASA, 2017a), sheep numbers from (SENASA, 2017c) and goat numbers from (SENASA, 2017b Vargas, 2013;Travaini et al, 2015. Two of these surveys covered four provinces excluding Tierra del Fuego, and two were carried out only in Santa Cruz provinces.…”
Section: Cattle Numbers Tabulated For Five Patagonian Provinces and 40mentioning
confidence: 99%
“…, Travaini et al . ), which represents an invaluable biological and cultural heritage in South America. This study supports the idea that the conservation of wide‐ranging species such as the Andean Condor requires a landscape approach.…”
Section: Discussionmentioning
confidence: 99%